Enrique the black - Danny Jalil (Penguin Books, 2021)
"Who was the man they called Enrique the Black? Taken from his family, and forced into slavery during the Portuguese invasion of Malacca in 1511, the Malay boy rechristened as Enrique must quickly to adapt to a new religion, and to the strange new lands of Portugal and Spain. A decade later his master Ferdinand Magellan, dreaming of fame and fortune, has an audacious plan to sail to the other side of the world, on a seemingly quick, uncharted route to the Moluccas Spice Islands. Enrique will prove invaluable once they arrive there, as he alone speaks the islanders' Malay language. What no one in Magellan's fleet can foresee though, is how giants, bad weather, mutiny and excruciating hunger haunt their every move. Even more dangerous however, is Magellan's own religious fervour, which threatens to undo the entire expedition once they arrive at the islands soon to be known as the Philippines, where Enrique will face certain death, and perhaps the chance to finally taste freedom"--Back cover.